Predictive value of ATRIA risk score for contrast-induced nephropathy after percutaneous coronary intervention for ST-segment elevation myocardial infarction - Aksoy,Fatih (2019)
SUMMARY BACKGROUND: The AnTicoagulation and Risk factors In Atrial fibrillation (ATRIA) risk score used to detect the thromboembolic and hemorrhagic risk in atrial fibrillation patients has been shown recently to predict poor clinical outcomes in patients with acute myocardial infarction (ACS), regardless of having atrial fibrillation (AF). We aimed to analyze the relationship between different risk scores and contrast-induced nephropathy (CIN) development in patients with ACS who underwent urgent percutaneous coronary intervention (PCI) and compare the predictive ability of the ATRIA risk score with the MEHRAN risk score. METHODS: We analyzed 429 patients having St-segment Elevation Myocardial Infarction (STEMI) who underwent urgent PCI between January 2016 and February 2017. Patients were divided into two groups: those with and those without CIN and both groups were compared according to clinical, laboratory, and demographic features, including the CHA2DS2-VASc and ATRIA risk score. Predictors of CIN were determined by multivariate regression analysis. Receiver operating characteristics (ROC) curve analysis was used to analyze the prognostic value of CHA2DS2-VASc and ATRIA risk score for CIN, following STEMI. RESULTS: Multivariate regression analysis showed that Athe TRIA risk score, Opaque/Creatinine Clearance ratio, and low left ventricular ejection fraction was an independent predictor of CIN. The C-statistics for the ATRIA risk score and CHA2DS2-VASC risk score were 0.66 and 0.64 (p<0.001, and p<0.001), respectively. A pair-wise comparison of ROC curves showed that both scores were not inferior to the MEHRAN score in predicting CIN. CONCLUSION: The ATRIA and CHA2DS2-VASC scoring systems were useful for detecting CIN following STEMI.